Transmitting and circulating the late antique and Byzantine worlds - Ivanova, Mirela; Jeffery, Hugh (The medieval mediterranean, 2019)
Front Matter --Copyright Page --Acknowledgments --Maps and Illustrations --Contributors --Introduction /Mirela Ivanova and Hugh Jeffery --Movement of People --Evidence for Female Pilgrims at Abu Mina /Grace Stafford --Travelling Painters’ Workshops in the Late Antique Levant: Preliminary Observations /Julia Burdajewicz --A New Pilgrimage Site at Late Antique Ephesus /Katinka Sewing --“Slavery” outside the Slave Trade /Adele Curness --Transmitting Traditions --‘This Shocking Lobster’: Understanding the Fantastic Creatures of the Armenian Alexander Romance /Alex MacFarlane --Mauropous as Menander’s Student of Rhetoric /Jovana Anđelković --Reappraising the Arabic Accounts for the Conflict of 446/1054–5 /Mathew Barber --The Apparition of Leo of Chalcedon /Peter Bara --Contact --The Evidence of Byzantine Sgraffito Wares in 12th-Century Sicily /Matteo G. Randazzo --Between East Rome and Armenia: Paulician Ethnogenesis c.780–850 /Carl Dixon --By Land or by Sea: Tracing the Adoption of Cotton in the Economies of the Mediterranean /Anna Kelley --Back Matter --Index.
Keywords: Konferenzschrift -- 24.-25.02.2017 -- Oxford; Geschichte 400-1250; Kulturvermittlung; Byzantinisches Reich; Spätantike